DEVELOPMENT AND VALIDATION OF ENGLISH GRADED READERS’ E-BOOKS BASED ON FOLKLORES FOR EXTENSIVE READING CLASSES FOR UNIVERSITY STUDENTS - Yuli Puji Astutik; Rudi Hartono; Mursid Saleh; Utami Widiati (English Review: Journal of English Education, 2025)
This study aimed to develop and validate English Graded Readers (GR) e-books based on local folklore to support the implementation of the Extensive Reading (ER) program at universities in East Kalimantan, Indonesia. Employing a Research and Development (R&D) approach, the study adopts the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) proposed by Dick et al. (2015). As a preliminary investigation, the present research focuses on the first three stages of the model: Analysis, Design, and Development. A total of 72 university students from four higher education institutions in East Kalimantan participated in the development process. The results of product development and expert validation demonstrated highly satisfactory results. Specifically, translation accuracy achieved a validity score of 90%, graded reading content received a perfect score of 100%, and media design and technical aspects obtained a validity score of 92%. These findings suggest that the developed e-books met a high standard of quality and can serve as a strong foundation for the subsequent stages of the R&D cycle, namely Implementation and Evaluation, to assess the product’s effectiveness in enhancing ER practices.